2011
DOI: 10.1016/j.vaccine.2011.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Missed clinical opportunities: Provider recommendations for HPV vaccination for 11–12 year old girls are limited

Abstract: Objective The purpose of this study was to determine the prevalence of physician recommendation of human papillomavirus (HPV) vaccination in early (ages 11-12), middle (13-17), and late adolescent/young adult (18-26) female patients by physician specialty, and to identify factors associated with recommendation in early adolescents. Methods A 38-item survey was conducted April 2009 through August 2009 among a nationally representative random sample of 1,538 Family Physicians, Pediatricians, and Obstetricians … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
190
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(203 citation statements)
references
References 34 publications
10
190
1
Order By: Relevance
“…30,45,47 Studies assessing the relationship between provider characteristics and HPV vaccine recommendations most often focused on clinical specialty and demographics. Most studies found that pediatricians reported more positive HPV vaccine recommendation practices than family physicians 9,11,12,30,33,[48][49][50][51] or other types of providers. 12,32 Other studies failed to find variation in recommendations by specialty, 23,[34][35][36]40,52,53 but several of these studies did not include pediatricians.…”
Section: Preferences In Communication Source By Provider Typementioning
confidence: 99%
See 3 more Smart Citations
“…30,45,47 Studies assessing the relationship between provider characteristics and HPV vaccine recommendations most often focused on clinical specialty and demographics. Most studies found that pediatricians reported more positive HPV vaccine recommendation practices than family physicians 9,11,12,30,33,[48][49][50][51] or other types of providers. 12,32 Other studies failed to find variation in recommendations by specialty, 23,[34][35][36]40,52,53 but several of these studies did not include pediatricians.…”
Section: Preferences In Communication Source By Provider Typementioning
confidence: 99%
“…12,32 Other studies failed to find variation in recommendations by specialty, 23,[34][35][36]40,52,53 but several of these studies did not include pediatricians. 34,52,53 Most studies did not find variation in HPV vaccine recommendations by provider sex, 9,23,30,36,39,44,[47][48][49]54 but those that did most often favored female providers. 24,25,29,33,53 Similarly, most studies did not find variation in HPV vaccine recommendations by provider age or years in practice, 30,33,36,47,49 although a few did with mixed results.…”
Section: Preferences In Communication Source By Provider Typementioning
confidence: 99%
See 2 more Smart Citations
“…Several HPV vaccines have been developed, including a bivalent (strains 16 and 18) and a quadrivalent (strains 16, 18, 6, and 11) vaccine (Harper et al, 2004;Villa et al, 2005;Harper et al, 2006). The Centers for Disease Control and Prevention's Advisory Committee on Immunization Practices (ACIP) recommends routine vaccination of girls aged 11-12 years, as well as for those aged 13-26 years who have not been previously vaccinated (Markowitz et al, 2007;Vadaparampil et al, 2011). A quadrivalent vaccine was licensed by the US Food and Drug Administration (FDA) for use in males 9 through 26 years of age in 2009 (American Academy of Pediatrics, 2012).…”
Section: Knowledge and Attitudes About Human Papillomaviruses And Immmentioning
confidence: 99%